Navigating Tuberculosis Treatment Challenges of Genetic Perspectives and DNA-Based Detection: A Literature Review - Rouly Pola Pasaribu; Zen Hafy; Ariesti Karmila; Nur Riviati; Zen Ahmad; Fadhyl Zuhry Lubis; Welly Salutondok (GLOBAL HEALTH SCIENCE GROUP, 2026)
Tuberculosis remains a major global health problem, particularly because of the increasing burden of drug-resistant tuberculosis (DR-TB), including MDR-TB and XDR-TB. Resistance in Mycobacterium tuberculosis is driven mainly by spontaneous genetic mutations, adaptive evolution, tolerance mechanisms, and host microenvironmental factors, which complicate both treatment and diagnosis. This review aimed to examine recent advances in the genetic mechanisms underlying antibiotic resistance in M. tuberculosis and to evaluate the progress of DNA-based detection technologies for tuberculosis diagnosis and management. This literature review analyzed 49 scientific articles published between 2012 and 2026 to examine the molecular and genetic basis of drug resistance in M. tuberculosis. The study focused on identifying target gene mutations, efflux pump mechanisms, compensatory evolution, and heteroresistance. Furthermore, it evaluated the clinical application of advanced DNA-based diagnostic tools, including GeneXpert, line probe assays, targeted next-generation sequencing (tNGS), whole-genome sequencing (WGS), droplet digital PCR, and CRISPR-based detection. Information was qualitatively synthesized to compare the efficacy and limitations of these modern diagnostic strategies in global tuberculosis management. Drug resistance was primarily associated with de novo mutations in genes such as rpoB, katG, inhA, pncA, gyrA/gyrB, and rrs/eis, as well as compensatory mutations that preserve bacterial fitness. In addition, non-genetic tolerance, dormancy, and efflux pump overexpression contributed to bacterial survival. DNA-based technologies enabled faster and more comprehensive resistance detection than conventional methods, although limitations remained in sensitivity, mutation coverage, cost, and infrastructure requirements. Genetic mutations, evolutionary adaptation, and tolerance mechanisms form the core basis of drug resistance in M. tuberculosis. Integrating DNA-based diagnostics into clinical practice is essential to improve early resistance detection, support personalised treatment, and reduce the spread of drug-resistant tuberculosis.